M&A under Uncertainty - Masafumi SHODA (AAOS Transactions)
This paper is a study that empirically examines the antecedents of M&A from the perspective of uncertainty in the business environment. In recent years, interest in corporate management under uncertainty has increased, as events that have a significant impact on the business environment of a wide range of companies occurred. Despite the recognition of the importance of M&A as a strategy to deal with environmental uncertainty, previous research has not shown clear results. Especially, there has been little research analyzing the M&A type selection by Japanese companies in relation to environmental uncertainty. Therefore, the research question of this study was set as “How does environmental uncertainty affect M&A implementation, diversification, and deal size?”. The analysis of M&A deals announced between 2004 and 2018 in which Japanese companies were the buyers suggested that when the uncertainty of the industry environment increases, small-scale M&A tends to be actively implemented. Based on the lean startup theory, when uncertainty is high, the speed of response is emphasized, and simple investment behavior takes precedence. The contribution of this study is that it adds new empirical results on the M&A type selection in an uncertain environment.